Treating shock with norepinephrine administered in midline catheters in an intermediary care unit: a retrospective cohort study - Gustav Torisson; Marcus Ohlsson; Hanna Karlsson; Ajnaz Afrasiabi; Viktor Månsson; Hannes Hartman (BMJ Open)
Objectives A rising incidence of septic shock as well as recommendations for early vasopressor initiation has increased the number of patients eligible for norepinephrine (NE). Traditionally, NE has been administered through central lines, in intensive care units, due to the risk of extravasation in peripheral lines. The aim of the current study is to determine the rate of complications and patient outcomes when NE is administered through midline catheters (MCs) in intermediary care units (IMCUs).Design Retrospective cohort study.Setting Three IMCUs in southern SwedenParticipants Patients with septic shock who received NE through a MC from September 2020 through March 2023.Primary and secondary outcome measures The primary outcome was a major complication to treatment, defined as extravasation of NE, catheter-associated venous thromboembolism and catheter-associated bloodstream infection (BSI). Secondary outcomes included patient outcomes after intermediary care (either deceased, discharged to regular ward care or intensive care) and the need for additional central lines.Results Of 474 eligible patients, 472 were included, with a median (IQR) age of 73.5 (65–80) years, with 281 (60%) men. The median (IQR) duration of NE infusion was 21 (9–38) hours, with a median (IQR) dosage of 0.12 (0.08–0.20) µg/kg/min. Major complications occurred in 12 cases (2.5%), with one suspected extravasation, seven thromboembolic events and four catheter-related BSIs. After intermediary care, 334 patients (71%) were discharged to regular ward care, 66 patients (14%) were escalated to intensive care and 72 (15%) died in intermediary care, of whom 69 had a documented ceiling of care decision. 100 patients (21%) received a central line.Conclusion NE administration in MCs was associated with a low rate of short-term complications and could decrease the need for central lines. MCs can enable the initial management of circulatory failure outside intensive care, but more studies are needed to determine the long-term value of IMCUs.Trial registration number NCT06121115.